Cytomegalovirus haemorrhagic colitis complicating COVID‐19 in an immunocompetent critically ill patient: A case report. Issue 5 (5th December 2020) - Leemans, Sophie; Maillart, Evelyne; Van Noten, Héloïse; Oliveira Dos Santos, Lucas; Leahu, Laura Maria; Kamgang, Prochore; Gallerani, Andrea; Clevenbergh, Philippe
Abstract: Suspicion threshold for opportunistic coinfections should be lowered in severe COVID‐19. Serum CMV polymerase chain reaction and colonoscopy should be discussed in presence of persistent digestive disturbances. Abstract : Suspicion threshold for opportunistic coinfections should be lowered in severe COVID‐19. Serum CMV polymerase chain reaction and colonoscopy should be discussed in presence of persistent digestive disturbances.